(untitled) (INNOVATIVE ECONOMY, 2026)
Voloshchuk K.B., Popovych K.-D.М. STRATEGIC GUIDELINES AND FUNCTIONALITY OF MANAGEMENT OF RECOVERY, SUSTAINABLE DEVELOPMENT, AND DIGITAL TRANSFORMATION OF EURO-INTEGRATED ENTREPRENEURSHIP Purpose. The aim of the article is to deepen the theoretical foundations of strategizing and management functionality as an innovative approach to recovery, sustainable development, searching for opportunities to increase export potential, and digital transformation of Euro-integrated entrepreneurship. Methodology of research. The following research methods were used: induction and deduction to reveal current trends in the benefits of digitalization, which outweigh its costs due to the growth of business investments in the digitalization of corporate processes at the global level; analysis and synthesis – to compare traditional and digital functionality of management of recovery, sustainable development and digital transformation of Euro-integrated entrepreneurship; calculation and construction – to determine the possibilities of increasing exports to the EU; abstract and logical – for the transformation of business models; tabular and graphical – for the visualization of the obtained research results. Findings. The key characteristics of traditional and digital approaches to the functional management of recovery, sustainable development, and digital transformation of European-integrated entrepreneurship are determined, as sources of competitive advantages and strategic guidelines for reducing costs, increasing productivity and flexibility of business, long-term sustainability, and development. Significant imbalances in the dynamics of the development of legal entities-enterprises and individual entrepreneurs by the number of business entities, the number of employed and hired workers, the specific weight in the total number, the results of innovative activity and activity of enterprises, and the volumes of exports and imports are established. Current trends reveal that the benefits of digitalization significantly outweigh its costs, especially in the medium and long term, thereby strengthening competitive positions in the market and allowing businesses to objectively assess efficiency, personalize offers, predict user behavior, and develop digital skills among personnel. The possibility of increasing business value by implementing sustainable practices of an ESG-oriented approach is identified, which allows responding to challenges, proactively using sustainable development as a strategic factor of differentiation, integrating it into the business strategy, and focusing simultaneously on social, environmental, and industry significance, which significantly affect operational activities and final results. Originality. Further development of the theoretical foundations of strategizing and functional management as an innovative approach to recovery, sustainable development, and digital transformation of European-integrated entrepreneurship based on the creation of ecosystems has been achieved; flexible approaches, interactive work, constant feedback, and rapid adaptation to changes, real-time decision-making, and search for opportunities to increase Ukraine’s export potential. Practical value. The obtained results can be used by authorities and management as strategic guidelines and innovative approaches to the management of the recovery, sustainable development, and digital transformation of entrepreneurship in the process of adaptation to the requirements of European integration. Significant opportunities to realize the unused potential of increasing Ukraine’s exports to the EU and to implement sustainable practices through an ESG-oriented approach aimed at creating business value have been identified. Key words: strategy, guideline, functionality, management, recovery, sustainable development, digitalization, transformation, European integration, entrepreneurship, enterprises.